New technologies, e-government and informality - Juan Chacaltana; Fernanda Bárcia de Mattos; Juan Manuel García Carpio (International Labour Organization (ILO), 2024)
This working paper studies the complex relationship between technology adoption and informality, leveraging recent cross-country data to analyse the effects of mobile phone subscriptions, internet access, automation and e-government on informal employment, vulnerable employment, and the shadow economy's GDP share. The study delves into the nuanced interplay between technology adoption and informality, suggesting that while technology adoption can reduce informality by enhancing productivity and government capacity, it can also create conditions to increase informality, such as the proliferation of own-account work for example. The paper empirically explores these forces and finds that e-government initiatives in the majority of cases reduce informality. However, while the potential of technology to reduce the shadow economy is clearer, addressing informal and vulnerable employment may require additional policy interventions. This research contributes to the understanding of the multifaceted and multidirectional relationship between technology and informality, and the potential for technology to enhance governance and public service delivery.
Keywords: 330; future of work; informal employment; employment policy; technology